2012
DOI: 10.1103/physrevx.2.021014
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-Controlled Ferromagnetism inSrTiO3

Abstract: Magnetotransport and superconducting properties are investigated for uniformly La-doped SrTiO 3 films and GdTiO 3 =SrTiO 3 heterostructures, respectively. GdTiO 3 =SrTiO 3 interfaces exhibit a highdensity 2D electron gas on the SrTiO 3 side of the interface, while, for the SrTiO 3 films, carriers are provided by the dopant atoms. Both types of samples exhibit ferromagnetism at low temperatures, as evidenced by a hysteresis in the magnetoresistance. For the uniformly doped SrTiO 3 films, the Curie temperature i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…Furthermore, it would be useful to investigate other related materials exhibiting the same phenomena. In particular, recent work on epitaxially grown GdTiO 3 -SrTiO 3 interfaces 53 indicates that ferromagnetism and superconductivity can also coexist in such systems. Being much cleaner than LAO/STO from a materials point of view, these interfaces might provide an attractive environment for the investigation of the ideas proposed in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it would be useful to investigate other related materials exhibiting the same phenomena. In particular, recent work on epitaxially grown GdTiO 3 -SrTiO 3 interfaces 53 indicates that ferromagnetism and superconductivity can also coexist in such systems. Being much cleaner than LAO/STO from a materials point of view, these interfaces might provide an attractive environment for the investigation of the ideas proposed in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…7, based on the phase diagram in Refs. [52][53][54]. Therefore, it is also important to understand when and why they do not occur.…”
Section: Discussionmentioning
confidence: 99%
“…The STO/GTO system has been studied extensively [15][16][17][18][19][20][21][22][23][24][25][26], and the 2DEG here has been found to exhibit extremely high carrier densities and ferromagnetic effects, with both electrostatic and doping modulation being observed to change the carrier properties. The proposed explanation for the 2DEG creation can be found in a simple charge transfer picture [7,14,16].…”
Section: (Sto) and The Ferromagnetic Mott Insulator Gdtio 3 (Gto)mentioning
confidence: 99%
“…4 Thin (<2 nm) quantum wells of SrTiO 3 embedded in GdTiO 3 show magnetoresistance hysteresis at low temperatures. 5 It was suggested that the proximity to the ferrimagnetic GdTiO 3 likely plays a role, but the magnetic state of the SrTiO 3 was not resolved. For example, it is possible that the SrTiO 3 quantum well has become magnetic due to exchange coupling.…”
mentioning
confidence: 99%
“…4 In contrast to GdTiO 3 , which is ferrimagnetic with a Curie temperature of ∼30 K in bulk 15 and ∼20 K in the samples with 4-nm GdTiO 3 , 5 SmTiO 3 is antiferromagnetic with a Néel temperature of ∼50 K. 16 Electrical and structural characterization, as well as growth details have been described elsewhere. 5,14,17,18 The carrier mobility was an order of magnitude higher than in conducting, doped GdTiO 3 or SmTiO 3 , showing that electrical transport occurs only in the SrTiO 3 quantum well [further evidence comes from magnetotransport; Seebeck measurements, which are SrTiO 3 -like; 19 and the band offsets, which favor charge transfer into the SrTiO 3 (Refs. 4 and 20)].…”
mentioning
confidence: 99%